الآراء الأصولية للحافظ العلائي : دراسة تحليلية - وينز، كمال (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2020)
This study deals with an important methodological position in the fundamental thought of al-Hafiz al-ʽAla'i. The study discusses about al-Hafiz al-ʽAla'i biography and his efforts in Usul al-Fiqh. Its further discusses and analyses the essentials of evidence in Shariah (Al-Adillah), its deductive rules, and methods of its application according to al-Hafiz al-ʽAla'. The study also focuses on the main al-ʽAla'isʼ contributions to the theory of jurisprudence, based on the intellectual capacity and the critical ability features of al-Hafiz al-ʽAla'i especially in the science of Hadith and language. The purpose of this study is to conduct a background and critical study on the opinions of Al-Hafiz Al-Alai on fundamental views and how to employ them in the jurisprudential branches in order to highlight the efforts of al-Hafiz al-ʽAlā'i and his contribution to this discipline. The researcher used the inductive method to identify the terminologies of the fundamentalist (Usuli) in his several literatures, which are either stated categorically or understood from the content of its usage, words and by explaining some based on the investigation of some jurisprudential branches on which he built his rulings. The researcher also used the critical analytical approach in analyzing the al-Hafiz al-ʽAla'I Usuli views which are deducted from his literature, and to subject them to scientific evaluation and criticism. Whereby the researcher compares his views and other Usuli's view on the theoretical jurisprudential scenario, and look into evidences of each view in order to know the most accurate view. The research has reached the following conclusions: Understanding the general jurisprudential approach of the al-Hafiz al- ʽAla'i, which is consistent with the comprehensive method between the school of theologist and jurists, identifying jurisprudential positions and contributions of al-ʽAla'i as included in the section of the disagreement between words and deeds with the report. Furthermore, the study shows the weight of his jurisprudential evidences that is considered based on the combination of statements and the concordance of the fundamental jurisprudential differences such as the Hadith al-Mursal and Ziyadatut al- Thiqat (forwarded traditions with extra trust). It also explains the two related opinions of Imam al-Shafi'i in eight discuss: basis of Ijma'a al-Sukuti “implicit Ijma'”, reference to Qawl Sahabi) Opinion of the companions), also on A'am (General injunction) whether its evidence is decisive (Qat'i) or probable (Zanni), whether prohibition indicate things void, and whether Muqtadha “the context” leads to general or not; and whether asking for details in probable situation should have general consideration or not? The indication of wawun (and) whether shows the plurality or concurrently, and whether consideration should be given to the generality of the statements or the specific of the incident. And lastly, the differences among Mujtahid whether the truth is one or not.